2021
DOI: 10.7717/peerj.11668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fertilization with reducing in nitrogen and phosphorous application on growth, yield and biomass accumulation of rice (Oryza sativa L.) under a dual cropping system

Abstract: The current farming system in China is heavily reliant on synthetic fertilizers, which adversely affect soil quality and crop production. Therefore, the aim of this study was to assess the effect of different nitrogen (N) and phosphorous (P) fertilizer application rate on the growth, yield, and yield components of rice cultivars in the Binyang, Beiliu and Liucheng sites of southern China in the early (March to July) and late season (August to December). The study consisted of three fertilization regimes—CK (N0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Conventional farming increases crop productivity but is heavily reliant on synthetic fertilizers and pesticide input Y. Li et al, 2016;Ullah et al, 2020;Wu et al, 2021). Excessive synthetic N fertilization causes significant environmental problems, such as increased greenhouse gas emissions and groundwater contamination, particularly leading to degradation of soil physicochemical and biological properties (Y.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional farming increases crop productivity but is heavily reliant on synthetic fertilizers and pesticide input Y. Li et al, 2016;Ullah et al, 2020;Wu et al, 2021). Excessive synthetic N fertilization causes significant environmental problems, such as increased greenhouse gas emissions and groundwater contamination, particularly leading to degradation of soil physicochemical and biological properties (Y.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, overpopulation has led to a greater demand for food; thus, increasing crop production on a sustainable basis is a difficult task in today's farming systems (Bitew & Alemayehy, 2017; Valin et al., 2014). Conventional farming increases crop productivity but is heavily reliant on synthetic fertilizers and pesticide input (Ali, He, et al., 2020; Y. Li et al., 2016; Ullah et al., 2020; Wu et al., 2021). Excessive synthetic N fertilization causes significant environmental problems, such as increased greenhouse gas emissions and groundwater contamination, particularly leading to degradation of soil physicochemical and biological properties (Y. Luo et al., 2020; Sarma et al., 2017; Y. Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Increase in N levels significantly delayed days to maturity Ayoub et al (1994). The delayed in days to maturity may be due to enough nutrient accessibility, which finally enhanced the growing time period of cereal crops Ullah et al (2021). Alike results were reported by Zeidan et al (2010) who reported that N fertilizer improves vegetative growth, increased light use efficiency and grain filling period.…”
Section: Discussionmentioning
confidence: 65%
“…Nitrogen is often the most deficient of all the plant nutrients. Nitrogen is the key element in achieving consistently high yields in cereals (Iqbal et al, 2019;Iqbal et al, 2020, Ali et al, 2020Wu et al, 2021, Ali et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…However, a huge quantity of agricultural biomass is burned in the field and buried in soil in southern China, which is not environmentally friendly since it harms soil fauna and degrades soil quality. Moreover, fertilizer management significantly affects rice biomass and its yield [ 5 , 6 , 7 ], and to improve rice yield and biomass, farmers excessively use chemical fertilizer, especially N, which is not eco-friendly [ 8 , 9 ]. To cope with this problem, many studies reported that biochar has the potential to decrease the requirement of N fertilizer without compromising rice yield and biomass [ 3 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%